Processes controlling the dispersion and beaching of floating marine debris in the Barcelona coastal region - Ivan Hernandez; Leidy M. Castro-Rosero; Leidy M. Castro-Rosero; Manuel Espino; Jose M. Alsina; Jose M. Alsina (Frontiers in Marine Science)
IntroductionCoastal areas are considered potential sinks for plastic in marine environments. Data from a Lagrangian numerical simulation at a coastal scale using high-resolution hydrodynamic information and observational data of river debris discharge were analysed to determine the environmental variables from meteorological forcing or coastline orientation contributing to particle beaching.MethodA beaching likelihood parameter was developed to quantitatively measure the propensity for an area to receive or accumulate particles from a known outflow source. Statistical analyses of particle beaching were conducted to reveal possible relationships with hydrodynamic variables. A debris mass budget was calculated from the river release observational data used in the simulation.ResultsAreas close to the release points received the highest amounts of particles and also registered the highest beaching likelihood values. Significant wave height mildly affected particle beaching (Pearson’s r=0.36). Relative perpendicular wave directions promoted beaching in coastlines with lower azimuths (vertical orientation), whereas those with higher azimuths (horizontal orientation) were more affected by relative alongshore wave directions. The mass contribution from river discharge on beaches where cleanup data was available was 6.0% of the total debris collected.DiscussionThe beaching likelihood parameter revealed the influence of coastal geometry on particle deposition in an area. Comparisons with other studies regarding beaching amounts and particle residence times are challenging due to the scale difference. The complexity of the beaching process makes it difficult to establish relationships with hydrodynamic variables, although a clear association between the coastline orientation and wave direction was established. The debris mass contribution from the two rivers included in the simulation was two orders of magnitude lower than indicated in other studies for the area.